A high-entropy alloy nano-enzyme, a biosensor, and a preparation method and application thereof

CN119926495BActive Publication Date: 2026-10-16CHONGQING MEDICAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510112495.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2026-10-16
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

目前,对HEAs类酶活性的研究较少,基于HEAs内在结构所赋予的催化活性,选择通过表面修饰进一步提高其类酶活性的相关报道尚不存在

Benefits of technology

[0051]To overcome the problems existing in the prior art, we introduced surface modification engineering on HEAs surfaces and investigated the effect of surface modification on their enzyme-like activity. Inspired by the adhesion properties of mussel foot proteins, polydopamine (PDA) coating has become a multifunctional surface modification strategy. PDA materials contain abundant catechol, imine, and amine groups, exhibiting excellent metal ion chelating capabilities, biocompatibility, hydrophilicity, and adhesion properties. This allows them to adhere firmly to different surfaces and provide stable interfaces for further functionalization. Simultaneously, PDA also possesses strong near-infrared absorption capabilities, generating photothermal conversion efficiency under 808 nm infrared light irradiation. Furthermore, PDA coatings have been shown to enhance nanozyme activity through induced accumulation and electron transfer effects. However, research on regulating the catalytic performance of nanozymes through a dual strategy of compositional adjustment and surface modification is rarely reported. The Sabatier principle suggests that a good catalyst should have appropriate binding strength with the key substrate to balance the coverage of adsorbed products, improve adsorption/desorption efficiency, and thus achieve optimal catalytic effects. The d-band center position of HEAs is closely related to the adsorption strength of the catalyst for the reactants. Based on the Sabatier principle and d-band center theory, high-entropy alloy catalysts can be designed in a targeted manner.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a high-entropy alloy nano-enzyme PDA-HEA with peroxidase-like activity, a biosensor based on the PDA-HEA, and a preparation method and application thereof. The preparation method of the high-entropy alloy nano-enzyme PDA-HEA comprises the following steps: S1, preparing PtRuFeCoNi HEA nanowires by a low-temperature oil phase method; and S2, synthesizing PDA-HEA: dispersing the PtRuFeCoNi HEA nanowires in a solvent B, adding dopamine and a Tris-HCl solution into the solvent B, stirring, stirring until the color of the solution becomes black, and centrifuging, so that the obtained precipitate is the PDA-HEA. The high-entropy alloy nano-enzyme PDA-HEA or the biosensor based on the PDA-HEA can be applied in detection of acetylcholinesterase, amino acid ester pesticides and organophosphorus pesticides, and is convenient to operate and high in detection sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of analytical chemistry, specifically to a high-entropy alloy nanozyme, a biosensor, its preparation method, and its application. Background Technology

[0002] Carbamates are a class of neurotoxins that inhibit acetylcholinesterase activity, preventing the breakdown of the neurotransmitter acetylcholine and leading to neuromuscular transmission disorders. Methomyl is a highly toxic oxime carbamate pesticide, widely used not only in common formulations but also as a compound formulation; it controls various pests by inhibiting acetylcholinesterase (AChE). Due to the widespread use of pesticides, monitoring pesticide residues in agricultural products and environmental substrates is undoubtedly crucial for ensuring food safety and ecological health.

[0003] Numerous laboratory-based techniques have been developed for the detection of carbamate pesticides, including gas chromatography, gas chromatography-mass spectrometry (GC-MS), high-performance liquid chromatography (HPLC), and liquid chromatography-tandem mass spectrometry (LC-MS). While these methods are technically mature and offer high accuracy and sensitivity, they still have limitations in analyzing biological samples containing carbamate pesticides. These limitations include expensive equipment, complex and time-consuming sample pretreatment, and the need for specialized laboratory personnel, significantly restricting their field application. Therefore, to further simplify sample analysis procedures, improve method selectivity and sensitivity, and achieve visualized and intelligent detection of biological samples, there is an urgent need to develop a simple, rapid, and immediate new method for detecting trace carbamate pesticide residues in fruit, vegetable, and environmental samples.

[0004] Nanozymes are a class of enzyme mimics that possess both the properties of nanomaterials and catalytic functions. They can mimic the functions of natural enzymes such as peroxidases and oxidases, and have many unique advantages, including low cost, high stability, ease of modification, tunable catalytic activity, and suitability for large-scale production. The unique physicochemical properties of nanomaterials provide important opportunities for regulating their catalytic performance. Therefore, nanomaterials are widely used in fields such as biochemical sensing, disease diagnosis and treatment, and environmental protection. Currently, various types of nanocatalyst materials have been developed, including metal-based nanozymes, carbon-based nanozymes, metal oxide / sulfide nanomaterials, and nanocomposite materials. Despite the significant progress made in nanozyme development, limited catalytic activity, complex catalytic mechanisms, and biocompatibility issues have become bottlenecks restricting their further development. Therefore, it is necessary to explore the development of novel nanozymes, design strategies to regulate their activity, and conduct in-depth research on their catalytic mechanisms. It is generally believed that the performance of nanozymes is closely related to the structural properties and electron distribution of their surface. Therefore, improving catalytic activity through surface modification engineering or modification with different ligands is an effective way to optimize and regulate catalysts.

[0005] High-entropy alloys (HEAs) are single-phase solid solution alloys with simple crystal structures, composed of five or more metals in equal or nearly equal proportions, with each element having an atomic ratio of 5-35%. In recent years, they have attracted widespread attention. Unlike traditional bimetallic and trimetallic alloys, HEAs possess significant mechanical properties. Therefore, research on HEAs mainly focuses on metallic structural materials. The subtle interactions between the internal geometry and electronic structure of HEAs endow them with unique characteristics. By rationally adjusting the preparation conditions to control the material composition and geometry, HEAs have broad application prospects and provide an effective means to improve their catalytic performance. There are various methods for synthesizing HEAs. Different methods have varying degrees of difficulty, resulting in different catalytic activities, dispersibility, and morphologies of the synthesized HEAs. Furthermore, catalytic activity and dispersibility are both affected by the type and proportion of metals. The atomic size differences among different elements in HEAs lead to significant lattice distortion, increasing the energy barrier for atomic diffusion, which is beneficial for the formation and stability of HEAs. In addition, the cocktail effect of HEAs regulates the adsorption of reactants and intermediates at active sites through the synergistic effect of multiple elements. Numerous studies have elucidated the mechanisms underlying the superior catalytic performance of HEAs using DFT calculations. These mechanisms primarily involve the d-orbital interactions of various metals within HEAs, creating more electron transfer channels and active centers for catalytic reactions, thus resulting in excellent electrocatalytic performance. Currently, research on the enzyme-like activity of HEAs is limited. Based on the catalytic activity conferred by the intrinsic structure of HEAs, there are no reports on further enhancing their enzyme-like activity through surface modification. Therefore, developing HEAs with more efficient enzyme activity can not only better leverage their catalytic performance but also provide impetus for the development of high-entropy nanozymes (HEAzymes), promoting exploration in the new field of nanoenzymology. Summary of the Invention

[0006] The purpose of this invention is to address the above-mentioned problems by providing a high-entropy alloy nanozyme, a biosensor, its preparation method, and its application.

[0007] To achieve its objective, the present invention employs the following technical solution:

[0008] The first aspect of this invention provides a method for preparing a high-entropy alloy nanoenzyme PDA-HEA with peroxidase-like activity, comprising the following steps:

[0009] S1. Preparation of PtRuFeCoNi HEA nanowires by low-temperature oil-phase method

[0010] Take metal precursors of Pt, Ru, Fe, Co, and Ni, structure directing agent, and reducing agent, add them to solvent A, mix thoroughly and evenly, heat the solution to 70-90℃ and maintain for 4-9 min under stirring, then heat the solution to 200-240℃ and maintain for 80-100 min, cool, centrifuge to collect the precipitate, wash with detergent, collect the precipitate, and dry to obtain PtRuFeCoNi HEA nanowires;

[0011] The metal precursor is an acetylacetone metal complex;

[0012] The structure directing agent is selected from hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and dodecyltrimethylammonium chloride;

[0013] The reducing agent includes Mo(CO)6 and glucose;

[0014] S2, Synthetic PDA-HEA

[0015] The PtRuFeCoNi HEA nanowires prepared in step S1 were dispersed in solvent B and thoroughly mixed. Dopamine and Tris-HCl solution were added to the mixture, and the mixture was stirred (magnetic stirring at 500-1000 rpm, preferably 800 rpm) until the solution turned black. The mixture was then centrifuged, and the resulting precipitate was the high-entropy alloy nanoenzyme PDA-HEA.

[0016] Preferably, in the preparation method, the mass ratio of each raw material is: metal precursor of Pt: metal precursor of Ru: metal precursor of Fe: metal precursor of Co: metal precursor of Ni: structure directing agent: Mo(CO)6: glucose is 6-10:8-12:4-8:4-8:4-8:50-70:60-72:8-12, and the mass-volume ratio of structure directing agent to solvent A is 50-70mg:3-5mL;

[0017] In step S1, after each raw material is added to solvent A, it is mixed uniformly by ultrasonication. The ultrasonic conditions are: power 100-400W, time 1.5-2.5h.

[0018] Solvent A is oleylamine;

[0019] The detergent is a mixture of ethanol and cyclohexane, preferably a mixture of ethanol and cyclohexane at a volume ratio of 7-11:1;

[0020] Solvent B is ethanol.

[0021] Preferably, in step S2, the raw materials are prepared in the following ratio: PtRuFeCoNi HEA nanowires, solvent B, dopamine, and 1M Tris-HCl solution: 1.5-2.5 mg: 6-12 mL: 0.2-0.4 mg: 0.8-1.2 mL (preferably 2 mg: 9 mL: 0.3 mg: 1 mL).

[0022] After the PtRuFeCoNi HEA nanowires were added to solvent B, they were thoroughly mixed by ultrasonic treatment. The ultrasonic conditions were: power 100-400W, time 20-40min. After all the raw materials were mixed, they were stirred for 5-7h until the solution turned black. After centrifugation, the precipitate obtained was the high-entropy alloy nanoenzyme PDA-HEA.

[0023] Preferably, the metal precursor raw materials are (Pt(a-cac)2), (Ru(acac)3), (Fe(acac)3), (Co(a-cac)3), and (Ni(acac)2), and the structure directing agent is hexadecyltrimethylammonium bromide.

[0024] A second aspect of the present invention provides a high-entropy alloy nanoenzyme PDA-HEA with peroxidase activity, which is prepared by any of the preparation methods described above.

[0025] A third aspect of the present invention provides a PDA-HEA-based biosensor, which is prepared by loading the above-mentioned high-entropy alloy nanoenzyme PDA-HEA onto a hydrogel; preferably, the hydrogel is sodium alginate hydrogel or hyaluronic acid silica gel.

[0026] A fourth aspect of the present invention provides a method for fabricating the above-described PDA-HEA-based biosensor, comprising the following steps:

[0027] S1. Take the hydrogel monomer, crosslinking agent, the high-entropy alloy nanoenzyme PDA-HEA, and water and mix them evenly to obtain a hydrogel mixture solution. The hydrogel monomer is selected from sodium alginate or sodium hyaluronate. The crosslinking agent of sodium alginate hydrogel is CaCl2. The raw materials of hyaluronic acid silicone gel include sodium hyaluronate and medical silicone.

[0028] The preferred hydrogel monomer is sodium alginate, and the crosslinking agent is CaCl2. The components in the hydrogel mixture are mixed in the following mass ratio: hydrogel monomer: crosslinking agent: PDA-HEA: water in a mass ratio of 6-10:0.10-0.14:0.010-0.014:1 (preferably 8:0.12:0.012:1).

[0029] Preferably, the hydrogel monomer is first added to water and heated to dissolve, then a crosslinking agent is added, mixed well, and then PDA-HEA is added and mixed well to obtain a hydrogel mixed solution;

[0030] S2. Add the prepared mixed solution into the mold and let it stand at 4-10°C to solidify and form the hydrogel-like biosensor.

[0031] The fifth aspect of the present invention provides the application of the above-mentioned high-entropy alloy nanoenzyme PDA-HEA or the above-mentioned PDA-HEA-based biosensor in the detection of acetylcholinesterase, amino acid ester pesticides, and organophosphorus pesticides; wherein the amino acid ester pesticides include methomyl, isoprocarb, aldicarb, and carbofuran.

[0032] The above-mentioned application method of high-entropy alloy nanozyme PDA-HEA for detecting acetylcholinesterase includes the following steps:

[0033] S1. Mix and incubate acetylcholinesterase solutions of known different concentrations with acetylthiocholine solutions. Add NaAc buffer, PDA-HEA, TMB solution and H2O2 solution to the incubated mixture to form the ATCh-TMB-H2O2 detection system. After the reaction is complete, measure the absorption spectrum (preferably at 652 nm).

[0034] S2. Obtain the absorbance corresponding to different concentrations of acetylcholinesterase solutions. Plot the concentration of acetylcholinesterase on the x-axis and the change in absorbance on the y-axis to obtain a standard curve of absorbance change versus concentration.

[0035] S3. Take the acetylcholinesterase to be tested and detect its absorbance using the same method. Calculate its concentration by comparing it with the absorbance change-concentration standard curve. The linear detection range of AChE is 0.1-1.1 mU / mL, and the detection limit is 0.064 mU / mL.

[0036] It is preferable to irradiate the PDA-HEA with an 808nm near-infrared laser for 4-6 minutes before proceeding with steps S1-S3.

[0037] The above-mentioned application method of high-entropy alloy nanoenzyme PDA-HEA for detecting methomyl includes the following steps:

[0038] S1. Mix and incubate a solution of acetylcholinesterase of known concentration with a solution of acetylthiocholine. Add different concentrations of methomyl, NaAc buffer, PDA-HEA, TMB solution and H2O2 solution to the incubated mixture to form an ATCh-TMB-H2O2 detection system. After the reaction is complete, measure the absorption spectrum (preferably at 652 nm).

[0039] S2. Obtain the absorbance corresponding to different concentrations of methomyl solution. Plot the concentration of methomyl on the x-axis and the change in absorbance on the y-axis to obtain the absorbance change-concentration standard curve.

[0040] S3. Take the methomyl to be tested and detect its absorbance using the same method. Calculate its concentration by comparing it with the absorbance change-concentration standard curve. The linear range for methomyl detection is 0.4-40, 150-1000 ng / mL, and the detection limit is 0.624 ng / mL.

[0041] Preferably, the PDA-HEA is irradiated with 808nm near-infrared laser for 4-6 minutes before proceeding with steps S1-S3; after irradiation with 808nm near-infrared laser for 4-6 minutes, the linear range of methomyl detection is 0.1-5, 10-2000 ng / mL, and the detection limit is 0.068 ng / mL.

[0042] The application method of the above-mentioned biosensor for detecting acetylcholinesterase includes the following steps:

[0043] ATCh and AChE standards of different concentrations were mixed and incubated to obtain a standard incubation solution. ATCh and the sample to be tested were mixed and incubated to obtain a sample incubation solution. The standard incubation solution and the sample incubation solution were then added dropwise to different detection units of the biosensor. H2O2 and TMB were then added, and the reaction was allowed to proceed fully. The color change of the gel in the detection unit was recorded. The content of AChE in the sample to be tested was determined and analyzed based on the color change of the detection unit after the addition of the standard incubation solution.

[0044] The above-mentioned application method for detecting methomyl using a biosensor includes the following steps:

[0045] AChE and ATCh were mixed and incubated. The incubation solution was then added to the biosensor. Methomyl, H2O2, and TMB were then added. Methomyl standards of different concentrations and the test sample were added to different detection units of the biosensor. After the reaction was complete, the gel color change of the detection unit was recorded. The content of methomyl in the test sample was determined and analyzed based on the color change of the detection unit after adding the methomyl standard.

[0046] The detection linear range of the biosensor for AChE is 0.1-12 mU / mL; the detection linear range of the biosensor for methomyl is 0.45-2 ng / mL.

[0047] The detection principle of the high-entropy alloy nanoenzyme and biosensor of this invention is as follows:

[0048] When used for acetylcholinesterase (AChE), if the analyte contains AChE, acetylthiocholine (ATCh) is specifically decomposed into thiocholine (TCh) by AChE. PDA-HEA exhibits peroxidase-like activity. When TCh binds to PDA-HEA, the sulfur atom in TCh coordinates with metal ions or other functional groups in the PDA-HEA enzyme, altering the enzyme's spatial structure or the properties of its active site. Simultaneously, TCh may compete with H₂O₂ for binding to the enzyme's active site, thereby inhibiting the decomposition of H₂O₂ and reducing the formation of ·OH. Therefore, TCh reduces the ability of PDA-HEA peroxidase-like enzymes to decompose H₂O₂ and generate hydroxyl radicals by interfering with their catalytic activity. Since no hydroxyl radicals oxidize colorless TMB to blue oxTMB, the solution does not change absorbance or the gel does not change color. Furthermore, because TCh can reduce hydroxyl radicals, it further synergizes with the phenomenon that TMB does not turn blue. That is, if the sample contains AChE, the sample will not turn blue; if the sample does not contain AChE, the sample will turn blue after the reaction.

[0049] When used to detect methomyl, the principle is that carbamate pesticides (such as methomyl) decompose AChE, thus ATCh is retained as a substrate. At this point, TCh is not generated and does not act on PDA-HEA. Therefore, PDA-HEA can decompose H₂O₂ into hydroxyl radicals, which oxidize TMB to blue oxTMB, turning the sample blue. In other words, if the sample contains methomyl, the sample turns blue; if the sample does not contain methomyl, the sample does not change color.

[0050] The beneficial effects of this invention are:

[0051] To overcome the problems existing in the prior art, we introduced surface modification engineering on HEAs surfaces and investigated the effect of surface modification on their enzyme-like activity. Inspired by the adhesion properties of mussel foot proteins, polydopamine (PDA) coating has become a multifunctional surface modification strategy. PDA materials contain abundant catechol, imine, and amine groups, exhibiting excellent metal ion chelating capabilities, biocompatibility, hydrophilicity, and adhesion properties. This allows them to adhere firmly to different surfaces and provide stable interfaces for further functionalization. Simultaneously, PDA also possesses strong near-infrared absorption capabilities, generating photothermal conversion efficiency under 808 nm infrared light irradiation. Furthermore, PDA coatings have been shown to enhance nanozyme activity through induced accumulation and electron transfer effects. However, research on regulating the catalytic performance of nanozymes through a dual strategy of compositional adjustment and surface modification is rarely reported. The Sabatier principle suggests that a good catalyst should have appropriate binding strength with the key substrate to balance the coverage of adsorbed products, improve adsorption / desorption efficiency, and thus achieve optimal catalytic effects. The d-band center position of HEAs is closely related to the adsorption strength of the catalyst for the reactants. Based on the Sabatier principle and d-band center theory, high-entropy alloy catalysts can be designed in a targeted manner.

[0052] This study designed and synthesized PtRuFeCoNi HEANWs with POD-like activity and modified the surface of HEA NWs with PDA. We investigated the changes in their catalytic performance and the effect of photothermal conversion on enzyme-like activity. Theoretical studies revealed the reason why PDA modification improves the catalytic performance of HEA. The Sabatier principle explains the increase in HEA enzyme activity after PDA coating, namely, optimizing the surface charge distribution, appropriately reducing d-band centers, balancing substrate adsorption, further improving adsorption / desorption efficiency, and enhancing catalytic performance. As a conceptual application, a PDA-HEA-based biosensor was constructed for the sensitive detection of acetylcholinesterase (AChE) and methomyl. PDA-HEA loaded with sodium alginate (SA) hydrogel, combined with a smartphone, enables portable visual detection. Attached Figure Description

[0053] Figure 1Synthesis and characterization of PtRuFeCoNi HEA: A) Schematic diagram of HEA formation process; B) HRTEM image of HEA; C) HRTEM image of PDA-HEA; D) XRD pattern; E) HRTEM image of PDA-HEA; Inset diagram showing atomic arrangement; F) FCC pattern on

[111] crystal axis of PDA-HEA (regions 1-3); G) HAADF-STEM-EDS spectrum and metal element content obtained by ICP-OES; H) HAADF-STEM-EDS mapping of PDA-HEA; I) FT-IR spectrum.

[0054] Figure 2 The peroxidase-like activity and optimization of HEA and PDA-HEA are shown: A) Schematic diagram of peroxidase-like activity assessment of PDA-HEA (using OPD, ABTS, and TMB); B) UV-Vis absorption spectra and visual colors of PDA-HEA for different colorimetric reactions; C) UV-Vis absorption spectra and visual colors of FeCoNi, RuFeCoNi, and HEA; D) PDA-FeCoNi, PDA-RuFeCoNi, and PDA-HEA; E) UV-Vis absorption spectra of PDA, HEA, and PDA-HEA; F) Absorbance spectra of different concentrations of dopamine over time; G) Absorbance spectra of different concentrations of PDA-HEA over time; H) Peroxidase-like activity and visual colors of PDA-HEA at different pH values; Data are presented as mean ± standard deviation (n = 6 independent samples).

[0055] Figure 3The effects of photothermal conversion on the POD-like activity and mechanism of PDA-HEA are shown: A) UV-Vis absorption spectra of HEA, PDA-HEA, and NIR-PDA-HEA; B) Time-varying absorption spectra of HEA, PDA-HEA, and NIR-PDA-HEA; C) Photothermal conversion performance of PDA-HEA at different concentrations; D) Effect of different temperatures on the POD-like activity of PDA-HEA; Data are presented as mean ± standard deviation (n = 6 independent samples); E) Control group (catalytic system without PDA-HEA), PDA, HEA F) UV-Vis absorption spectra of PDA and PDA-HEA; the legend includes insets of infrared thermograms of these four systems; G) UV-Vis absorption spectra of control group (catalytic system without PDA-HEA), PDA, HEA and PDA-HEA under NIR irradiation; the legend includes insets of infrared thermograms of these four systems under NIR irradiation; H) UV-Vis absorption spectra of PDA-HEA at 50°C and room temperature (under dark conditions); H) Temperature-time thermograms of infrared thermograms of PDA, HEA and PDA-HEA under NIR irradiation, with a time range of 0-5 minutes.

[0056] Figure 4 The peroxidase-like mechanisms of HEA, PDA-HEA, and NIR-PDA-HEA are shown: AC) Michaelis-Menten curves of HEA, PDA-HEA, and NIR-PDA-HEA at different concentrations of TMB; data are presented as mean ± standard deviation (n = 6 independent samples); DF) Michaelis-Menten curves of HEA, PDA-HEA, and NIR-PDA-HEA at different concentrations of H2O2; data are presented as mean ± standard deviation (n = 6 independent samples). Presented in the form of G) specific activities of HEA, PDA-HEA and NIR-PDA-HEA; H) ESR spectra of ·OH generated by H2O2; data are presented as mean ± standard deviation (n = 3 independent samples); I) absorbance in PDA-HEA+TMB systems containing different scavengers; for superoxide dismutase (SOD) (ae: 0, 5, 10, 15 and 20 U / L), tryptophan (ae: 0, 0.5, 1, 1.5 and 2 mM) and isopropanol (ae: 0, 0.1, 0.5, 1 and 1.5 mM).

[0057] Figure 5The following are theoretical calculations using DFT to determine the electronic distribution, structural configuration, and POD-like mechanism of HEA and PDA-HEA: A) 3D atomic model of PDA-HEA crystal structure; B) Different reaction pathways of H2O2 decomposition to produce ·OH on HEA and PDA-HEA; C) Adsorption of H2O2 by PDOSs and partially amplified HEA; E) Comparison of d-band centers for single elements and the whole HEA; FG) Adsorption of PDOSs and partially amplified H2O2 on PDA-HEA; H) Comparison of d-band centers for single elements and batch PDA-HEA; I) Sabatier principle schematic diagram of HEA and PDA-HEA; J) Free energy spectra of H2O2 decomposition along homolytic cleavage pathway on HEA and PDA-HEA.

[0058] Figure 6 This study demonstrates a colorimetric detection platform for acetylcholinesterase (AChE) and methemocarb: A) AChE-controlled colorimetric reaction based on TMB+PDA-HEA nanozyme, illustrating the detection mechanism of AChE and methemocarb; B) UV-Vis absorption spectra of different compounds in the PDA-HEA / TMB / H2O2 system to investigate the feasibility of AChE detection; C) UV-Vis spectra of different concentrations of AChE; D) The relationship between absorbance change at 652 nm and AChE concentration, and its linearity; E) Different compounds... The feasibility of methomyl detection was investigated by examining the UV-Vis absorption spectra of the PDA-HEA / TMB / H2O2 system; F) UV-Vis spectra of methomyl at different concentrations; G) Relationship between absorbance change at 652 nm and methomyl concentration and its linear relationship; H) UV-Vis spectra of methomyl at different concentrations (under near-infrared light); I) Relationship between absorbance change at 652 nm and methomyl concentration and its corresponding linear relationship (under near-infrared light); J) Interference experiment of methomyl colorimetric detection platform.

[0059] Figure 7The following diagrams illustrate the construction of a comprehensive and portable detection platform for hydrogel@PDA-HEA: A) Schematic diagram of hydrogel@PDA-HEA synthesis and construction of a portable methomyl detection platform; B) Digital photographs of hydrogel, hydrogel@PDA, and hydrogel@PDA-HEA under white light; C) SEM image of hydrogel@PDA-HEA; red circles indicate that PDA-HEA is located inside the hydrogel; D) Relationship between B / G and methomyl concentration and the corresponding linear relationship; the inner part shows digital photographs of different concentrations of methomyl detected by hydrogel@PDA-HEA; E) Relationship between B / R and AChE concentration and the corresponding linear relationship; the inner part shows digital photographs of different concentrations of AChE detected by hydrogel@PDA-HEA; F) Digital photographs of hydrogel@PDA-HEA, TMB, OPD, and ABTS in different shapes (strawberry, pear, apple) under white light. Detailed Implementation

[0060] The present invention will be further described below with reference to embodiments, but these embodiments are not intended to limit the scope of the invention.

[0061] Unless otherwise specified, the experimental methods described in the following examples are conventional methods.

[0062] Example 1

[0063] 1. Reagents and Materials

[0064] Ruthenium acetylacetonate (Ru(acac)3), platinum acetylacetonate (Pt(acac)2), ferric acetylacetonate (Fe(acac)3), nickel acetylacetonate (Ni(acac)2), cobalt acetylacetonate (Co(acac)3), oleylamine (OAm), trimethylammonium bromide (CTAB), molybdenum hexacarbonylmolybdenum (Mo(CO)6), glucose, and acetylthiocholine (ATCh) were purchased from Macklin Biotechnology (Shanghai) Co., Ltd. 2,2'-aza-bis(3-ethylbenzothiazol-6-sulfonic acid) diammonium salt (ABTS), 3,3',5,5'-tetramethylbenzidine (TMB), and o-phenylenediamine (OPD) were obtained from Shanghai Aladdin Biotechnology Co., Ltd. Ethanol and H2O2 (30%) were obtained from Chongqing Chuandong Chemical Co., Ltd. Acetylcholinesterase (AChE) and NaAc buffers (pH 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 0.2M) were purchased from Shanghai Yuanye Biotechnology Co., Ltd. (Shanghai, China). Horseradish peroxidase (HRP), glucose oxidase (GOx), neutral protease (NEP), and acid phosphatase (ACP) were obtained from Shanghai SigmaAldrich Trading Co., Ltd. (Shanghai, China). Bovine serum albumin, fraction V, and heat shock isolation (BSA) were purchased from Sangon Biotech Co., Ltd. (Shanghai). Metformin (CAS No. 16752-77-5) was purchased from LGC Labor GmbH Bgm (Augsburg, Germany). All reagents were not further purified. All experimental aqueous solutions were prepared with distilled water.

[0065] 2 methods

[0066] 2.1 Synthesis of FeCoNi NPs, RuFeCoNiNPs and HEANWs

[0067] HEANWs synthesized this data based on previous reports and made slight modifications. Follow these steps:

[0068] In a flask containing OAm (4 mL), CTAB, transition metal organometallic complex raw material, Mo(CO)6, and glucose were added sequentially. The mixture was sonicated at room temperature for 2 h (power 100-400 W) to obtain a homogeneous solution. The solution was then heated to 80 °C and held for 5 min with magnetic stirring in an oil bath, followed by heating to 220 °C and holding for 90 min. The mixture was rapidly cooled to room temperature and centrifuged to collect the black product. The product was washed multiple times with an ethanol / cyclohexane mixture (v / v: 9:1). Finally, the precipitate was lyophilized and stored for later use. FeCoNi NPs and RuFeCoNi NPs were synthesized under the same conditions and process, differing only in composition.

[0069] The raw materials for the synthesis of FeCoNi NPs are: CTAB (60mg), Fe(acac)3 (6mg), Co(acac)3 (6mg), Ni(acac)2 (6mg), Mo(CO)6 (66mg) and glucose (10mg).

[0070] The raw materials for the synthesis of RuFeCoNiNPs are: CTAB (60mg), (Ru(acac)3) (10mg), Fe(acac)3 (6mg), Co(acac)3 (6mg), Ni(acac)2 (6mg), Mo(CO)6 (66mg) and glucose (10mg).

[0071] The raw materials for synthesizing HEANWs (i.e., PtRuFeCoNi HEA nanoparticles) are: CTAB (60mg), (Ru(acac)3) (10mg), (Pt(acac)2) (8mg), Fe(acac)3 (6mg), Co(acac)3 (6mg), Ni(acac)2 (6mg), Mo(CO)6 (66mg) and glucose (10mg).

[0072] 2.2 Synthesis of PDA-FeCoNi NPs, PDA-RuFeCoNi NPs, and PDA-HEANWs:

[0073] Follow these steps: Add 2 mg of the HEANWs prepared in the previous step to 9 mL of ethanol and sonicate (100-400 W) for 30 min; add 30 μL of dopamine (10 mg / mL) to 1 mL of Tris-HCl solution (1 M, pH 8.5) and mix well, then add this mixture to the ethanol solution of HEANWs and stir vigorously (800 rpm). The color of the solution will slowly transition from light brown to black. After stirring continuously for 6 hours, dissolve the residue obtained by centrifugation in ultrapure water to obtain PDA-HEANWs.

[0074] PDA-FeCoNi NPs and PDA-RuFeCoNi NPs were synthesized using the same method.

[0075] 2.3 HEANWs, Characteristics of PDA-HEANWs

[0076] TEM and HRTEM images were characterized using a FEI Tecnai G2 F20 TEM instrument (FEI, USA). AC-STEM images and EDS plots were obtained using a JEM-arm300f (JEM, Japan). Powder XRD patterns were recorded on an X-ray diffractometer (D8 Advance, Bruker, Germany). XPS data were retrieved using a K-Alpha X-ray photoelectron spectroscopy (XPS) spectrometer from Thermo Fisher Scientific, USA. The composition of HEANWs was determined using ICP-OES (720ES, Agilent, USA). FT-IR data in the wavenumber range of 400–4000 cm⁻¹ were measured using a Nicolet IS50 Fourier transform infrared (FT-IR) spectrometer (Thermo Fisher Scientific, USA). Electron spin resonance (ESR) data were obtained using an electron paramagnetic resonance spectrometer (A300-10 / 12, Bruker, Germany). Zeta potentials were assessed using Zetasizer nano-ZS90 (Malvern, UK). UV-Vis absorption spectra were obtained using a UV-Vis spectrophotometer (TU-1901, PERSEE, China). Absorbance at 652 nm was measured for all experimental groups using a microplate reader (Multiskan Go, Thermo Fisher Scientific, USA).

[0077] The configurational entropy of a high-entropy alloy is defined by the following formula:

[0078]

[0079] ΔS configuration >1.5R represents a high-entropy material; ΔS configuration 1.0–1.5R represents a medium-entropy material; ΔS configuration <1.0R indicates a low-entropy material.

[0080] In this invention, ΔS of HEANWs configuration =1.85R, and is classified as a high-entropy material.

[0081] 2.4 Enzyme-like activities of HEANWs, PDA-HEANWs, and NIR-PDA-HEANWs

[0082] The POD-like activity of HEA and PDA-HEANWs was detected using the TMB colorimetric method. Specifically, TMB (8 μL, 10 mg / mL) was added to each sample. -1 Add 5 μg of H2O2 (2 μL, 30%) to 2 mL of pH 4.5 NaAc buffer (0.2 M), which contains 5 μg of H2O2. -1HEANWs or PDA-HEANWs. Absorbance was measured at 652 nm at room temperature after a 5-minute reaction period. NIR-PDA-HEANPs were irradiated with an 808 nm near-infrared laser for 5 min. Different concentrations (1, 2, 3, 4, 5, and 6 μg / mL) were used. -1 Different pH values ​​(3.5–7.0) and different power densities (0.2–1.2 W / cm³) -2 The optimal enzyme activity conditions for HEANPs were determined by analyzing PDA-HEANPs.

[0083] NIR-PDA-HEANWs refers to nanozymes formed by irradiating PDA-HEANPs with an 808nm near-infrared laser for 5 minutes.

[0084] 2.5 Enzyme kinetics studies of HEANWs, PDA-HEANWs and near-infrared PDA-HEANWs

[0085] Kinetic measurements were performed in time-course mode by monitoring changes in absorbance at 652 nm. Peroxidation reactions were carried out using different concentrations of TMB (0.1–2.0 mM) and H₂O₂ (1.0–10 mM). In each experiment, HEANWs or PDA-HEANWs (5 μg / mL) were used. -1 The solution containing H2O2 and TMB substrate was added to NaAc buffer (pH 4.5, 0.2M, 2mL). Additionally, the absorbance at 652nm was measured by irradiating the NIR-PDA-HEA NWs with an 808nm near-infrared laser for 5 min. The Michaelis-Menten constant (Km) was determined using a Lineweaver-Burk plot, employing the double reciprocal of the Michaelis-Menten equation:

[0086] v = v max ×[S] / (K m +[S]),

[0087] Where v represents the initial reaction rate, v max [S] represents the maximum reaction rate, [S] represents the substrate concentration, and K represents the maximum reaction rate. m This is the Michaelis constant.

[0088] 2.7 Determination of specific activity

[0089] A series of concentrations of HEANWs or PDA-HEANWs were mixed with H2O2 (2 μL, 30%) and TMB (8 μL, 10 mg / mL). -1The nanozyme was mixed in 2 mL of NaAc buffer (pH 4.5, 0.2 M), and the initial reaction rate was calculated by the change in absorbance of the TMB (Δa / Δt). Additionally, the absorbance at the nanozyme concentration was measured after irradiating it with an 808 nm near-infrared laser for 5 min. The specific activity was determined using a linear fitting curve of nanozyme concentration versus initial reaction rate.

[0090] 2.8 ESR Measurement

[0091] Electron spin resonance (ESR) spectroscopy was used to measure hydroxyl radicals (·OH) and superoxide anions (·O). 2- ) and singlet oxygen ( 1 The generation of H2O2. In short, the test was performed under the following conditions, including H2O2, DMPO, and HEANWs or PDA-HEANWs. All mixtures were dispersed in NaAc buffer (0.2M) at pH 4.5. After reacting for 10 min at room temperature, the solution was immediately subjected to ESR analysis. Additionally, the same procedure was performed after irradiating NIR-PDA-HEANWs with an 808 nm near-infrared laser for 5 min.

[0092] 2.9 Colorimetric Detection of Acetylcholinesterase in Solution

[0093] After incubating 5 μL of different concentrations of AChE and 10 μL of LATCH (acetylthiocholine) (10 mM) at 37 °C for 30 min, 1970 μL of NaAc buffer (pH 4.5, 0.2 M) and 5 μL of HEA NWs or PDA-HEANWs (2 mg / mL) were added to the mixed solution. -1 The NIR-PDA-HEANWs were reacted with H2O2 (2 μL, 30%) and 8 μL TMB (10 mmol / L) for 30 min at 25 °C. The absorption spectra were then measured. Additionally, the NIR-PDA-HEANWs were irradiated with an 808 nm near-infrared laser for 5 min, followed by the same procedure.

[0094] 2.10 Colorimetric Determination of Methomyl in Solution

[0095] After incubating 5 μL LATCHE (0.55 mU / mL) and 10 μL LATCH (10 mM) at 37 °C for 30 min, add 5 μL of methomyl at different concentrations, 1965 μL of NaAc buffer (pH 4.5, 0.2 M), and 5 μL of HEA NWs or PDA-HEANWs (2 mg / mL) to the mixed solution. -1The NIR-PDA-HEANWs were reacted with H2O2 (2 μL, 30%) and 8 μL TMB (10 mmol / L) at 25 °C for 30 min, and the absorption spectra were measured. The same procedure was also performed after irradiating the NIR-PDA-HEANWs with an 808 nm near-infrared laser for 5 min.

[0096] 2.11 Construction of a portable colorimetric platform for acetylcholinesterase and methomyl hydrogel

[0097] To prepare the hydrogel, 8 mg of sodium alginate (SA) was added to a 5 mL glass bottle containing 1 mL of ultrapure water and stirred in a 60 °C water bath for 15 minutes. Under continuous stirring, 20 μL of CaCl2 (6 mg / mL) was added, and the mixture was stirred for another 15 minutes to achieve homogeneity. Subsequently, 6 μL of PDA-HEANWs (2 mg mL⁻¹) was added to the mixture. The mixture was then poured into a 96-well plate mold (300 μL per well) and refrigerated for 12 hours to form the assay hydrogel Hydrogel@HEzymes@PDA.

[0098] For AChE detection, 5 μL of different concentrations of AChE and 10 μL of LATCH (10 mM) were incubated at 37 °C for 30 min, and then added to a 96-well plate containing Hydrogel@HEzymes@PDA. Subsequently, 2 μL of H2O2 (30%) and 50 μL of TMB (10 mM) were added and reacted for 5 min. Color information was captured using a smartphone camera, and the images were converted into numerical data using ImageJ software, thus enabling quantitative analysis of AChE.

[0099] Similarly, for the detection of methomyl, 5 μL of LAChE (0.55 mU / mL) and 10 μL of LATCh (10 mM) were incubated at 37°C for 30 minutes, and then added to a 96-well plate containing Hydrogel@HEzymes@PDA. Next, 5 μL of different concentrations of methomyl, 2 μL of H₂O₂ (30%), and 50 μL of TMB (10 mM) were added, and the reaction was allowed to proceed for 5 minutes. The colors were recorded using a smartphone camera, and the images were processed using ImageJ software to obtain numerical values, thus enabling quantitative analysis of methomyl.

[0100] We first evaluated the enzyme-like activity of HEA using a colorimetric method, with 3,3',5,5'-tetramethylbenzidine (TMB) as the substrate. In the presence of H₂O₂, HEA can convert colorless TMB into blue oxidized TMB (oxTMB), and its characteristic absorption peak was monitored at 652 nm using UV-Vis absorption spectroscopy. Furthermore, the peroxidase (POD)-like activity of HEANWs was verified using 2,2'-adiazono(3-ethylbenzothiazol-6-sulfonic acid) diammonium salt (ABTS) and o-phenylenediamine (OPD), demonstrating the good substrate versatility of HEANWs. For comparison, we successfully prepared FeCoNi and RuFeCoNi with fewer metal precursors using the same synthetic method. By comparing the POD-like activities of the three materials, we found that the catalytic performance gradually increased. Studies have shown that noble metals outperform conventional metals; therefore, we hypothesize that the improved enzyme activity is attributed to the doping of noble metals, while the dramatic lattice distortion endows HEANWs with excellent POD-like activity. To demonstrate the universality of PDA modification and coating, we successfully coated FeCoNi, RuFeCoNi, and HEANWs surfaces with PDA. Notably, the catalytic performance of PDA-FeCoNi, PDA-RuFeCoNi, and PDA-HEA was significantly improved compared to unmodified materials. Thanks to the excellent hydrophilicity and biocompatibility of PDA, the solubility of PDA-HEA in water was significantly enhanced. To eliminate the influence of PDA, we synthesized a pure PDA phase without HEANWs and investigated its POD-like activity. The results showed that pure PDA lacked catalytic ability, while the catalytic activity of PDA-HEANWs exhibited a "1+1>2" effect compared to pure HEA and PDA. Furthermore, by varying the concentration of dopamine added during the formation of the PDA-coated HEANWs, the resulting samples exhibited different POD-like activities. When a higher concentration of dopamine was added, the enzyme-like activity decreased significantly. This may be because the excessive and thick PDA coating masked the active sites of the nanozyme, affecting the catalytic performance. Based on this, the optimal coating concentration was selected.

[0101] 3 Results and Analysis

[0102] 3.1 Characteristics of PtRuFeCoNi HEA nanowires and PDA-HEA nanozymes

[0103] PDA-HEA nanozymes are a type of HEA-based growth strategy that employs dopamine-mediated growth (e.g., ... Figure 1 As shown in Figure A). First, PtRuFeCoNi HEA nanowires were prepared using a simple low-temperature oil-phase method (as shown in Figure A). Figure 1 B. Figure 1C). We used platinum(II) acetylacetonate (Pt(acac)2), ruthenium(III) acetylacetonate (Ru(acac)3), iron(III) acetylacetonate (Fe(acac)3), cobalt(III) acetylacetonate (Co(acac)3), and nickel(II) acetylacetonate (Ni(acac)2) as metal precursors, OAm as solvent, hexadecyltrimethylammonium bromide (CTAB) as structure directing agent, and molybdenum hexacarbonyl (Mo(CO)6) and glucose as reducing agents. HEA nanowires were then dispersed in anhydrous ethanol by adding Tris-HCl solution and dopamine. During this process, dopamine (DA) itself was oxidized and aggregated to form PDA, which was then used to modify the surface of the HEA nanowires. This is crucial because the surface of PDA contains abundant catechol, imine, and amine groups, giving it excellent metal ion chelating properties. The three characteristic peaks in the X-ray diffraction (XRD) pattern of the HEA nanowires belong to the face-centered cubic (fcc) structure of FePt (PDF#02-1167). Figure 1 D). The diffraction peak intensity of PDA-HEA is significantly higher than that of HEA, which is likely due to the encapsulation of PDA. Compared with the diffraction peaks of pure Pt, Ru, Fe, Co, and Ni, the positions of the broad diffraction peaks have shifted significantly, proving that these metals have been incorporated into the HEA nanowire structure, forming an fcc structure. High-resolution transmission electron microscopy (HRTEM) images of HEA nanowires show an average intergranular spacing of 0.223 nm. Figure 1 E), corresponding to the (111) crystal plane of FePt, is consistent with the XRD results. Meanwhile, the integration intensity of the (111) lattice within the selected region indicates that the average lattice spacing determined by Fast Fourier Transform (FFT) analysis varies between region 1 (0.223 nm), region 2 (0.224 nm), and region 4 (0.225 nm) (S2), thus proving the presence of lattice distortion in the synthesized HEA. Furthermore, selected area electron diffraction (SAED) of the high-entropy nanowires further confirms its typical face-centered cubic structure. Figure 1 F), which is consistent with the results of XRD and HRTEM. All of these data indicate the successful combination of HEA nanowires.

[0104] Energy-dispersive X-ray spectroscopy (EDS) images from HEA showed that the five elements were uniformly distributed throughout the nanowire. ICP results showed that the relative atomic ratios of Pt, Ru, Fe, Co, and Ni were 26:20:19:7:28. Figure 1 G). Calculations show its configurational entropy to be 1.83R, which falls within the high-entropy range. These results demonstrate that the nanowire conforms to the conceptual definition of a high-entropy alloy and belongs to the category of high-entropy materials. Clearly, the EDS data from PDA-HEA also show the presence of a coating. Figure 1H).

[0105] Because DA is rich in catecholamines, and PDA, as an oxidative polymerization product of DA, also retains this structure, the changes in surface chemical bonds of HEA nanowires after PDA encapsulation were analyzed using Fourier Transform Infrared Spectroscopy (FTIR). Figure 1 I). The diffraction peak intensity of PDA-HEA was higher than that of HEA, and out-of-plane distortion of the CH bond in the aromatic ring was observed, confirming the successful modification of PDA.

[0106] X-ray photoelectron spectroscopy (XPS) was used to observe the metal distribution on the surfaces of HEA and PDA-HEA. The peaks of Pt 4f7 / 2 and Pt4f5 / 2 were attributed to 71.12 eV and 74.46 eV, respectively, while the peaks of Ru 3p3 / 2 and Ru 3p1 / 2 were attributed to 463.15 eV and 485.02 eV, respectively. The peaks of Fe 2p3 / 2 and Fe 2p1 / 2 were attributed to 712.09 eV and 724.45 eV, respectively, while the peaks of Co 2p3 / 2 and Co 2p1 / 2 were attributed to 780.91 eV and 796.79 eV, respectively. The peaks of Ni 2p3 / 2 and Ni 2p1 / 2 were attributed to 855.75 eV and 873.45 eV, respectively. The results indicate that HEA contains five metals: Pt, Ru, Fe, Co, and Ni, with different valence states. However, XPS results from PDA-HEA showed a significant decrease in peak intensity signals for each metal element, while the signal intensity for C increased. Furthermore, Zeta potential analysis of both HEA and PDA-HEA revealed a change in potential from positive to negative, further demonstrating that the PDA was successfully coated on the HEA surface (S5).

[0107] 3.2 Peroxidase-like enzyme activities of HEA and PDA-HEA

[0108] We first assessed the enzymatic activity of HEA using a colorimetric method, with 3,3',5,5'-tetramethylbenzidine (TMB) as the substrate. In the presence of H₂O₂, HEA can convert colorless TMB into a blue color. OX TMB was used, and the characteristic absorption peak at 652 nm was monitored by UV-Vis absorption spectroscopy. Furthermore, we verified the catalase-like activity of HEA using 2,2'-diphenylindoline-3-sulfonate ammonium salt (ABTS) and o-phenylenediamine (OPD), demonstrating that the HEA nanozyme has good substrate versatility (S6). For comparison, we also successfully synthesized FeCoNi and RuFeCoNi containing fewer metal precursors using the same synthetic method. By comparing the catalase-like activities of the three materials, the catalytic performance showed a progressively improving effect. Previous studies have demonstrated that noble metals outperform ordinary metals (…). Figure 2C), therefore we speculate that the improvement in enzyme activity is due to the incorporation of noble metals and the severe lattice distortion that gives HEA superior catalase-like activity.

[0109] To illustrate the universality of PDA modification and coating, we successfully applied PDA coatings to the surfaces of FeCoNi, RuFeCoNi, and HEA. Furthermore, compared to unmodified materials, the catalytic performance of PDA-FeCoNi, PDA-RuFeCoNi, and PDA-HEA was significantly improved. Figure 2 D). It is worth noting that the catalytic activity of nanozymes is generally related to their degree of dispersion. Thanks to the excellent hydrophilicity and biocompatibility of PDA, PDA-HEA exhibits significantly higher solubility in water than HEA. Therefore, the enhanced dispersibility makes it easier for active sites to bind to the substrate, thereby improving catalytic performance. To eliminate the influence of PDA, we synthesized pure-phase PDA without HEA and investigated its POD-like activity. The results showed that pure PDA did not possess catalytic activity (…). Figure 2 E), while the catalytic activity of PDA-HEA is greater than that of pure HEA and PDA ("1+1>2"). Simultaneously, by varying the concentration of added dopamine during the preparation of PDA-coated HEA nanozymes, samples exhibiting significant catalase (POD)-like activity can be obtained. When the added dopamine concentration is high (0.07 mg / mL-0.1 mg / mL), the enzyme-like activity decreases significantly. This may be due to the formation of an excessive and thick PDA coating, which masks the active sites of the nanozyme and affects its catalytic performance. Therefore, based on this result, the optimal coating concentration (0.03 mg / mL) was selected. With increasing PDA-HEA concentration, the absorbance also increases accordingly. Based on this result, a suitable material concentration was selected. Similarly, in the pH-dependent test, when determining the optimal pH value, we found that only limited OXD-like activity was observed compared to POD-like activity. Therefore, the influence of OXD-like activity can be essentially ignored.

[0110] 3.3 Photothermal conversion effect of PDA-HEA on POD-like activity and its mechanism

[0111] Due to the molecular structure and physical properties of PDA, when used as a coating, PDA not only enhances the POD-like activity of HEA but also endows it with photothermal conversion properties. Inspired by this mechanism and the fact that the decomposition of H2O2 is affected by temperature, we investigated the influence of the mechanism by which PDA-HEA exhibits its photothermal conversion properties on its pod-like activity. Figure 3 As can be directly seen from Figure A, the catalytic activity of HEA gradually increases after PDA modification and NIR treatment. Furthermore, the absorbance at 652 nm also increases with prolonged irradiation time. Figure 3B) Preliminary results indicate that the near-infrared treated PDA-HEA exhibits enhanced pod-like activity. Subsequently, the effect of different catalyst concentrations on the photothermal conversion effect was investigated, demonstrating that the photothermal conversion effect is related to the material concentration. Figure 3 C). Furthermore, the PDA-HEA exhibited excellent photothermal conversion stability, with no significant change in concentration after four on / off laser irradiation cycles. To further optimize its photothermal conversion performance, the laser irradiation power was also fine-tuned.

[0112] To elucidate the mechanism by which near-infrared irradiation enhances catalytic activity, we employed a water bath heating method instead of near-infrared treatment. At a water bath temperature of 50°C, we observed an increase in absorbance similar to that observed with previous NIR treatments, which is consistent with the results of temperature optimization. Figure 3 (D and 3G). These results indicate that the increase in pod-like activity after near-infrared treatment stems from the increase in ambient temperature. By comparing the absorbance values ​​of different PDA concentrations in dark and near-infrared environments, the effect of PDA on the photothermal conversion performance of PDA-HEA was analyzed. We found that the higher the PDA concentration, the greater the corresponding increase in activity. Simultaneously, the photothermal conversion effect intensity of PDA, HEA, and PDA-HEA was compared, and temperature changes were recorded using a thermal imager. Figure 3 The results showed that HEA had only limited photothermal conversion capability, while PDA and PDA-HEA both exhibited good photothermal conversion capabilities. This also proves that the photothermal conversion effect of PDA-HEA mainly comes from the modification of PDA. Furthermore, we compared the absorbance and temperature changes in the blank and colorimetric systems after the addition of PDA, HEA, and PDA-HEA under dark and near-infrared treatments, respectively. Figure 3 (E and 3F). We found that although PDA itself possesses photothermal conversion properties, considering the amount of catalyst added and the lack of pod-like activity in PDA, the absorbance and temperature of the entire system remained essentially unchanged after NIR treatment. This further illustrates that only when PDA encapsulates HEA within the reaction system can the most ideal effect be achieved. Crucially, near-infrared treatment not only increased the temperature of the PDA-HEA microenvironment but also promoted the decomposition of H2O2, increasing the diffusion rate of free radicals, thereby further enhancing catalytic activity. Finally, we investigated the stability of HEA and PDA-HEA, as well as their photothermal conversion capabilities. After 30 days at room temperature, the catalytic ability and photothermal conversion performance of both catalysts showed no significant changes, indicating that both catalysts exhibited good stability.

[0113] 3.4 Kinetic determination and free radical analysis of nanozymes

[0114] To evaluate the effects of PDA-encapsulated particles and near-infrared irradiation on enhanced pod-like activity, we modified TMB ( Figure 4AC) and H2O2 ( Figure 4 The concentration of DF was used to determine the enzyme kinetics, and the curve of substrate concentration versus initial reaction rate was obtained. It conforms to the classic Michaelis-Menten model, indicating that the pod-like catalytic process follows the Michaelis kinetic law.

[0115]

[0116] Based on the calculations using the above formula, the Lineweaver-Burk double reciprocal plot reveals the Michaelis constant (KM) and maximum reaction rate (vmax) of the corresponding substrate, and derives the catalytic constant (Kcat) and catalytic efficiency (Kcat / KM). It is generally believed that the key first step in the catalytic mechanism of nanomaterials mimicking pod-like activity is the adsorption of H2O2 onto nanozymes, catalyzing the decomposition of H2O2 to release free radicals that then react with the chromogenic substrate. Constructing nanozymes with better affinity for H2O2 is therefore of great significance. Compared to HEA, PDA-HEA exhibits a lower KM and a higher vmax for H2O2, indicating that the PDA coating can enhance the affinity and catalytic rate of HEA for H2O2. More importantly, compared to treatment under dark conditions, near-infrared irradiation of PDA-HEA further improves its affinity and catalytic rate for H2O2. Furthermore, Kcat represents the ability of a single enzyme molecule to catalyze the conversion of a substrate into a product per unit time. A higher Kcat value indicates stronger intrinsic catalytic activity. Kcat / Km represents the number of substrate molecules that each enzyme molecule can convert per second under substrate saturation conditions. A higher value indicates higher catalytic efficiency. Compared to HEA, PDA-HEA showed a 2.74-fold and 3.19-fold increase in Kcat and Kcat / Km for H2O2, respectively. Compared to PDA-HEA under dark conditions, near-infrared irradiation further increased Kcat and Kcat / Km by 1.86-fold and 2.06-fold, respectively (Table 1). This indicates that PDA modification and near-infrared irradiation gradually improved the catalytic ability of the nanozyme. Similarly, we compared the relevant kinetic parameters with TMB (Table 2). Compared to HEA, PDA-HEA showed a 4.43-fold and 1.97-fold increase in Kcat and Kcat / Km, respectively. Furthermore, compared to PDA-HEA under dark conditions, near-infrared treated PDA-HEA showed a 2.79-fold and 1.21-fold increase in Kcat and Kcat / Km, respectively. The catalytic activity of these nanozymes was further evaluated by specific activity (NIR-treated PDA-HEA: 13.87 U mg⁻¹, PDA-HEA: 7.33 U mg⁻¹, HEA: 1.75 U mg⁻¹) Figure 4(G). In summary, these results demonstrate the feasibility of our strategy of modifying the HEA surface with PDA and progressively enhancing enzyme-like activity with near-infrared assistance.

[0117] Table 1. Kinetic parameters of POD-like properties of HEANWs, PDA-HEANWs, and NIR-PDA-HEANWs with H2O2.

[0118]

[0119] Table 2. Kinetic parameters of POD-type performance of HEANWs, PDA-HEANWs, and NIR-PDA-HEANWs compared to TMB.

[0120]

[0121] To better analyze the catalytic mechanism of PDA-HEA, the possible types of reactive oxygen species (ROS) generated during H2O2 catalysis were discussed, generally producing ·OH, 1O2, and ·O2-. Isopropanol, tryptophan, and superoxide dismutase (SOD) were used as scavengers for ·OH, 1O2, and ·O2-, respectively. With increasing concentrations of the three scavengers, the relative catalytic activity of PDA-HEA gradually decreased, suggesting the possible presence of ·OH, 1O2, and ·O2-. Figure 4 I). To verify these experimental results, we further analyzed the types of free radicals generated during the catalytic process using ESR spectroscopy. The results showed that ·OH, 1O2, and ·O2- were generated, and the signal intensity gradually increased with time, mutually verifying the results of the free radical scavenger experiment. Simultaneously, without the addition of H2O2, the signals of the three free radicals were almost undetectable, indicating that PDA-HEA has almost no oxd-like activity, consistent with previous pH optimization results. Figure 4 G).

[0122] DFT calculations for 3.5HEA and PDA-HEA nanozymes

[0123] Previous experiments have shown that PDA modification significantly improves the catalytic performance of HEA. It is noteworthy that the catalytic activity of nanozymes is often closely related to their surface properties and the electronic structure of active sites. To further understand the reasons for the enhanced pod-like activity of PDA-HEA, we conducted theoretical studies on HEA and PDA-HEA using DFT calculations. Based on the characterization results from ICP, XRD, and other methods, we selected the HEA structure and reaction sites with the lowest energy and best stability as the theoretical model, and designed a PDA-HEA model accordingly. The total density of states (TDOS) indicates that both PDA-HEA and HEA exhibit abundant electron distribution near the Fermi level (EF). After PDA modification, the electronic structure of HEA changed, with a higher electron abundance at EF.

[0124] Subsequently, we analyzed the active sites of the HEA and PDA-HEA using the partial predicted density of states (PDOS), revealing the synergistic effects between different metals. First, there is significant overlap between the d orbitals of different metals, indicating strong intermolecular interactions. Fe, Co, and Ni, the three transition metals, exhibit a broad band in the middle with significant orbital overlap, verifying the strong coupling of the three-dimensional orbitals of transition metals. Furthermore, the Pt-5d orbital is located near -5 eV, the farthest orbital from the EF. This suggests that surface Pt acts as an electron reservoir during catalysis, balancing the valence state of the HEA. Notably, Ru's highest peak is at -2.2 eV, closest to the EF, while Pt also has a sharp peak near the EF. The electronic structure of the Pt-Ru bimetallic site enhances the electron density at the EF, which is more conducive to substrate adsorption and transfer. Therefore, the synergistic complementarity between the three transition metals and the Pt-Ru bimetal in the HEA leads to lattice distortion and inhomogeneity of the bonded orbitals in the HEA. Through electron transfer and orbital hybridization, it provides abundant active sites for its catalytic activity. In addition, PDA-HEA also exhibits a similar metal element distribution trend, indicating that the modification of PDA does not affect the internal element binding and synergistic effect of HEA.

[0125] Figure 5E and 5H depict the overall structure of HEA and PDA-HEA and the d-band centers of the five internal metal elements. According to the d-band center theory, for HEA, Ru (spin up, 0.39 eV; spin down, 0.98 eV), the higher the d-band center position, the stronger the adsorption of reactants. This is because the electron cloud is farther from the electron nucleus, more "diffuse," and more easily reacts with molecules. Crucially, Pt's d-band center is at a lower energy level (spin up, -0.656 eV; spin down, -0.446 eV), with a higher electron cloud density, indicating that it is more likely to donate electrons in catalytic reactions, promoting electron transfer, consistent with its role as an electron reservoir. The d-band model determines the electron donor-acceptor positions of metals. The Pt-Ru dual-site d-band centers exhibit significant differences, with Ru centers having higher energy and Pt centers having the lowest. This energy difference provides the impetus for electron transfer from Ru to Pt, a fact confirmed by experimental electron transfer experiments. The self-complementary induction between these two metals leads to more stable adsorption of the substrate and its intermediates. The transition metals Fe, Co, and Ni have higher energies in the spin-down state and lower energies in the spin-up state. These transition metals can synergistically interact with Pt-Ru to promote electron transfer and exert catalytic effects. After PDA modification, although the overall trend of the d-band centers of the metal elements in the catalyst remains unchanged, compared to HEA, the overall structure of PDA-HEA and the d-band centers of the five metals become more negative. This indicates that the electron density on the surface of PDA-HEA is relatively increased compared to HEA, making it easier to dissociate and transform the substrate while maintaining stable adsorption. Furthermore, the more negative d-band centers of PDA-HEA alter the donor-acceptor properties between it and the substrate, making it easier to donate / accept electrons, enhancing electron transfer, and facilitating the reaction. Therefore, PDA modification has no effect on the internal structure of HEA. Instead, it fine-tunes the d-band center of HEA and optimizes the surface electron cloud density, further improving its catalytic performance.

[0126] The pod-like activity mechanisms of PDA-HEA and HEA were further explored. According to the study, the catalytic decomposition of H2O2 involves two cleavage mechanisms: homogeneous decomposition and heterogeneous decomposition, such as... Figure 5As shown in Figure B, under the catalysis of PDA-HEA and HEA, H2O2 undergoes homolytic and heterolytic decomposition, ultimately generating ·OH, which catalyzes the oxidation of TMB to blue. We first compared the TDOS spectra of PDA-HEA and HEA after H2O2 adsorption. The electron density at EF of PDA-HEA is higher than that of HEA. Similar results were also found in the TDOS data of PDA-HEA and HEA after the decomposition and adsorption of ·OH. These results demonstrate that, compared with HEA, PDA-HEA has more electronic states available for electron occupation and electronic transitions. To evaluate the adsorption capacity of PDA-HEA and HEA for H2O2 in more detail, the PDOS plots clearly show that when H2O2 is adsorbed on the surfaces of PDA-HEA and HEA, the s and p orbitals of the adsorbed H2O2 have significant overlap with the D orbitals of the adjacent metals, indicating that both catalysts can stably adsorb H2O2. Figure 5 (C, D and 5F, G). Furthermore, similar results were observed for the adsorption of intermediate ·OH on PDA-HEA and HEA.

[0127] Based on the dissociation mechanism of H2O2, we calculated the Gibbs free energy changes at each step of the catalytic process, providing a more intuitive comparison of the catalytic activities of the two catalysts. Figure 5 As shown in Figure J, the adsorption energies of both HEA and PDA-HEA are negative (HEA, -0.754 eV; PDA-HEA, -0.279 eV), further demonstrating that both can stably adsorb H2O2. According to the Sabatier principle, for an ideal catalyst, the adsorption of reactants on the catalyst surface cannot be too strong or too weak. Excessive adsorption will cause reactants to be adsorbed too tightly, which is not conducive to the desorption of products. Conversely, weak adsorption is not conducive to the adsorption of reactants. PDA modification makes the d-band center more negative, optimizing the adsorption state of reactants and intermediates. It ensures that the adsorption is not too stable, preventing decomposition and dissociation, nor too weak to effectively catalyze decomposition, thus achieving the optimal catalytic state. Figure 5 I) Subsequently, the peroxide bonds in H2O2 break uniformly, generating two ·OH ( Figure 5J). Crucially, the rate-determining step (RDS) of the catalytic decomposition of H2O2, i.e., the slowest step, is the key factor determining the catalytic reaction rate. The superiority of this catalyst lies in the lower activation energy of its RDS, particularly the step with the highest energy barrier for the formation of ·OH from the OH* intermediate. The energy barrier crossed by the rate-determining step (RDS) for the homogeneous decomposition of H2O2 to ·OH in PDA-HEA is significantly lower than that in HEA (PDA-HEA, ΔE = 0.741; HEA, ΔE = 2.207), which may explain the faster catalytic rate of PDA-HEA. We also investigated the free energy changes of each step in the heterogeneous decomposition of H2O2 catalyzed by both catalysts. Similarly, for PDA-HEA, the energy barrier required for the formation of the first ·OH is higher (ΔE = 1.062), representing the rate-determining step (RDS) for the heterogeneous decomposition of H2O2. For HEA, the energy barrier required for the RDS of the heterogeneous decomposition of H2O2 is (ΔE = 1.785). This indicates that PDA-HEA still exhibits good catalytic performance in the heterogeneous decomposition of H2O2.

[0128] Overall, for HEA, the RDS from heterolytic decomposition is lower than that from homolytic decomposition, indicating that catalysis in HEA may be achieved through the catalytic decomposition of H2O2 to generate ·OH. For PDA-HEA, the RDS from homolytic decomposition is lower than that from heterolytic decomposition, suggesting that homolytic decomposition of H2O2 plays a dominant catalytic role in PDA-HEA. Of course, regardless of whether it's homolytic or heterolytic decomposition, the energy barrier required for PDA-HEA to catalyze the decomposition of H2O2 RDS is lower than that of HEA. The DFT results clarify the relationship between PDA modification improving the catalytic performance of HEA and the Sabatier principle: optimizing the charge distribution on the HEA surface and appropriately reducing the energy of the d-band centers balances product coverage, improving adsorption-dissociation efficiency, and thus enhancing its pod-like activity.

[0129] 3.6 Construction of a PDA-HEA-based biosensor

[0130] Acetylcholinesterase (AChE) can terminate the signal transmission of neurotransmitters in the synaptic cleft. Acetylthiocholine (ATCh), a widely used biomarker for disease diagnosis and treatment as well as biosensing, can be specifically broken down by AChE into thiocholine (TCh). TCh, as a strong reducing agent, can reduce blue oxTMB to colorless TMB. Based on this principle, to explore the potential applications of PDA-HEA, we constructed a PDA-HEA-based biosensor for the visual detection of AChE. Figure 6 A). For example Figure 6 As shown in Figure B, when ATCh and AChE coexist, the absorbance of the chromogenic system at 652 nm decreases significantly, indicating that ATCh and AChE alone have little effect on the catalytic activity of PDA-HEA. To optimize the performance of this biosensor, the concentration of acetylcholinesterase was optimized. With increasing AChE concentration, the absorbance of oxTMB gradually decreased. Figure 6 C). Within the AChE content range of 0.1–1.1 mU / mL, it showed a good linear relationship with the change in absorbance (ΔA652), and the limit of detection (LOD) was 0.064 mU / mL. Figure 6 (D) Compared to previously reported AChE detection sensing platforms, it exhibits an ultra-low LOD, which further demonstrates the excellent catalytic performance of PDA-HEA. Subsequently, the specificity of AChE detection was investigated. Horseradish peroxidase (HRP), glucose oxidase (GOx), neprilysin (NEP), acid phosphatase (ACP), papain, and bovine serum albumin (BSA) were selected as interfering substances. The influence of these proteins on the absorbance of the colorimetric system in the presence / absence of AChE was essentially negligible, indicating that this sensing platform exhibits good specificity for AChE detection.

[0131] Compared to amino acid ester pesticides, numerous nanozyme-based sensing platforms for the detection of organophosphorus pesticides (OPs) have been developed. Amino acid ester pesticides are widely used globally for pest and disease control in crops such as fruits and vegetables. They can accumulate in the environment and can damage the human central nervous system by inhibiting acetylcholinesterase (AChE) activity. Therefore, their detection is of great significance. Based on the inhibitory effect of amino acid ester pesticides on acetylcholinesterase, we selected methomyl as a typical carbamate pesticide and used the biosensor constructed in this paper to detect it. Figure 6 As shown in E, the introduction of pure methomyl had virtually no effect on the absorbance change, eliminating its own interference. With increasing methomyl concentration, the activity of AChE decreased, and subsequently the suppressed absorbance recovered. Figure 6 F). Methomyl showed good linearity in the concentration ranges of 0.4–40 and 150–1000 ng / mL, with a LOD of 0.624 ng / mL. Figure 6 G). Furthermore, this method outperforms other methods in detecting methomyl. Considering the complexity of real-world environments, we investigated the specificity of methomyl detection and selected different ions and other types of pesticides as interfering substances. Figure 6 J). Similarly, the sensor exhibits considerable selectivity in the presence / absence of these interfering substances.

[0132] In addition, to investigate the role of photothermal conversion in methomyl detection, we performed the same detection procedure as described above under NIR conditions. The linear range for methomyl detection using this sensing platform under NIR processing was 0.1–5 and 10–2000 ng / mL, with a LOD of only 0.068 ng / mL, which is 10 times lower than that without NIR irradiation. Figure 6 These results all indicate that the photothermal conversion effect enhances the catalytic performance of PDA-HEA, thereby improving the sensitivity of methomyl detection.

[0133] 3.7 Portable Detection Platform Based on Water-in-Gel@PDA-HEA and Smartphone

[0134] Sodium alginate (SA) is a natural polysaccharide derived from seaweed, exhibiting low irritation and toxicity to organisms. SA contains a large number of carboxyl groups. 2+ In the presence of these components, the G units (guluroaldehyde units) on the SA molecular chain will react with Ca. 2+ A cross-linking reaction occurs, forming a three-dimensional network hydrogel structure that immobilizes the nanozyme and chromogenic reagent within, acting as a size sieving mechanism to ensure the stability of color development. Furthermore, the high hydrophilicity and hydration capacity of SA make its response to target analytes more sensitive and rapid. Based on this, we chose SA hydrogel to encapsulate PDA-HEA (Hydrogel@PDA-HEA) in a 96-well plate and integrated it with a smartphone to construct a portable high-throughput detection platform (such as...). Figure 7 (As shown in A). Figure 7 B demonstrates the construction and injectability of Hydrogel@PDA-HEA. Color changes were observed with the addition of TMB and H2O2, while the addition of PDA-HEA had minimal impact on color development, thus proving the feasibility of using the Hydrogel@PDA-HEA sensor for colorimetric detection. SEM images obtained through freeze-drying revealed the internal morphology of the SA hydrogel, showing a favorable porous structure. SEM images of Hydrogel@PDA-HEA also exhibited a similar porous network structure. Upon magnification, a black PDA-HEA loading could be observed within the cavities (…). Figure 7 C). Thanks to the ultrastructure of PDA-HEA, loading PDA-HEA is relatively easy and will not damage the original structure of the hydrogel, which lays the foundation for Hydrogel@PDA-HEA to exert its catalytic performance.

[0135] In a 96-well plate containing Hydrogel@PDA-HEA, TMB and H2O2 were added sequentially, followed by the gradual introduction of ATCh and different concentrations of AChE. The resulting color signal gradually weakened. Signals were captured by taking photos with a smartphone, and RGB analysis was performed on the color information from the images. Figure 7 As shown in Figures D and E, the B / R value exhibits an excellent linear relationship with the AChE concentration within the range of 0–12 mU / mL. Similarly, upon adding methomyl to the above, the color development of Hydrogel@PDA-HEA gradually recovered with increasing methomyl concentration. The B / G value of methomyl showed a good linear relationship within the range of 0–2 ng / mL. These results confirm the feasibility of the visualization biosensing platform constructed based on Hydrogel@PDA-HEA. Interestingly, thanks to the three-dimensional network structure and molecular chain flexibility of the hydrogel, Hydrogel@PDA-HEA can be cross-linked and cured using different molds to obtain hydrogel products consistent with the mold shape. Considering that methomyl is mainly used in agricultural applications, we cleverly designed Hydrogel@PDA-HEA into the shapes of strawberries, pears, and apples, and used TMB, OPD, and ABTS as chromogenic substrates, successfully applying it to the detection of methomyl. Figure 7 F).

[0136] 4. Conclusion

[0137] In summary, we initially designed and synthesized PtRuFeCoNi HEA nanoparticles. Subsequently, we employed a surface modification strategy to modify the HEA surface with PDA, further enhancing enzyme-like activity through photothermal conversion. DFT results elucidated the reasons for the improved catalytic performance based on the Sabatier principle and PDA modification. Building upon the inherent structure of HEA, PDA coating shifts the d-band center downwards, increasing surface electron abundance and enhancing electron mobility, thereby promoting substrate adsorption-desorption conversion and improving catalytic efficiency. Furthermore, we utilized PDA-HEA as a biosensor to analyze acetylcholinesterase and methomyl, and established a smartphone-assisted hydrogel detection platform to achieve rapid and visual detection. In conclusion, this paper introduces the PDA surface modification strategy into the field of high-entropy nanozymes, verifying the relationship between the Sabatier principle and the photothermal conversion effect that enhances POD-like activity, providing a new perspective for the design and application of complex high-entropy nanozymes.

[0138] Example 2 Specific Application

[0139] To verify the feasibility and practicality of PDA-HEANWs in real samples, the residues of methomyl in pears, apples, and strawberries were analyzed. The accuracy of the detection method was evaluated using spiked recovery. Sample pretreatment was required before detection, as follows: 2 mg of pear was placed in 10 mL of ethanol solution, shaken thoroughly for 5 minutes, and then sonicated for 2 hours. Subsequently, 5 μL of LATCH (0.55 mU / mL), 10 μL of LATCH (10 mM), and 5 μL of different concentrations of methomyl were incubated at 37 °C for 30 min. Then, 1965 μL of fruit supernatant, 5 μL of PDA-HEANWs (2 mg mL⁻¹), 2 μL of H₂O₂ (30%), and 8 μL of TMB (10 mM) were added to the mixture. The absorbance spectrum was measured after reacting at 25 °C for 30 minutes. The treatment for apples and strawberries was the same.

[0140] Table 3. Results of PDA-HEA detection of methomyl in actual samples.

[0141]

[0142] Table 3 a Recovery rate (%) = 100 × (c 平均检测量 -c0) / c 加标量 ).

[0143] As shown in Table 3, the recovery rate for the detection of methomyl in actual samples was above 95%, and the relative standard deviation was within 3.5%. This demonstrates that the nanozyme detection method of this invention has considerable feasibility and practicality in actual samples, and provides a promising prospect for portable detection of carbamate pesticides.

Claims

1. A method for preparing a high-entropy alloy nanoenzyme PDA-HEA with peroxidase-like activity, characterized in that, Includes the following steps: S1. Preparation of PtRuFeCoNi HEA nanowires by low-temperature oil-phase method Take metal precursors of Pt, Ru, Fe, Co, and Ni, structure directing agent, and reducing agent, add them to solvent A, mix thoroughly and evenly, heat the solution to 70~90℃ and maintain for 4~9 min under stirring, then heat the solution to 200~240℃ and maintain for 80~100 min, cool, centrifuge to collect the precipitate, wash with detergent, collect the precipitate, and dry to obtain PtRuFeCoNiHEA nanowires; The metal precursor is an acetylacetone metal complex; The structure directing agent is selected from one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and dodecyltrimethylammonium chloride; The reducing agent includes Mo(CO)6 and glucose; S2, Synthetic PDA-HEA The PtRuFeCoNi HEA nanowires prepared in step S1 were dispersed in solvent B and mixed thoroughly. Dopamine and Tris-HCl solution were added to the mixture, and the mixture was stirred until the solution turned black. After centrifugation, the precipitate obtained was the high-entropy alloy nanoenzyme PDA-HEA.

2. The preparation method according to claim 1, characterized in that: The mass ratio of each raw material is as follows: metal precursor of Pt: metal precursor of Ru: metal precursor of Fe: metal precursor of Co: metal precursor of Ni: structure directing agent: Mo(CO)6: glucose is 6-10 : 8-12 : 4-8 : 4-8 : 4-8 : 50-70 : 60-72 : 8-12, and the mass-volume ratio of structure directing agent to solvent A is 50-70 mg : 3-5 mL; In step S1, after each raw material is added to solvent A, it is mixed uniformly by ultrasonication. The ultrasonic conditions are: power 100-400 W, time 1.5-2.5 h. Solvent A is oleylamine; The detergent is a mixture of ethanol and cyclohexane; Solvent B is ethanol.

3. The preparation method according to claim 1, characterized in that: In step S2, the raw materials are prepared according to the following ratio: PtRuFeCoNi HEA nanowires, solvent B, dopamine, and 1 M Tris-HCl solution: 1.5-2.5 mg : 6-12 mL : 0.2-0.4 mg : 0.8-1.2 mL. After the PtRuFeCoNi HEA nanowires were added to solvent B, they were thoroughly mixed by ultrasonic treatment. The ultrasonic conditions were: power 100-400 W, time 20-40 min. After all the raw materials were mixed, they were stirred for 5-7 h until the solution turned black. After centrifugation, the precipitate obtained was the high-entropy alloy nanoenzyme PDA-HEA. The metal precursor materials are Pt(acac)2, Ru(acac)3, Fe(acac)3, Co(acac)3 and Ni(acac)2, and the structure directing agent is hexadecyltrimethylammonium bromide.

4. A high-entropy alloy nanoenzyme PDA-HEA with peroxidase activity, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 3.

5. A biosensor based on PDA-HEA, characterized in that: It is prepared by loading the high-entropy alloy nanoenzyme PDA-HEA as described in claim 4 onto a hydrogel.

6. The PDA-HEA-based biosensor according to claim 5, characterized in that: The hydrogel is sodium alginate hydrogel or hyaluronic acid silica gel.

7. The method for fabricating the PDA-HEA-based biosensor according to claim 5, characterized in that, Includes the following steps: S1. Take the hydrogel monomer, crosslinking agent, the high-entropy alloy nanoenzyme PDA-HEA as described in claim 4, and water, mix them evenly to obtain a hydrogel mixed solution, wherein the hydrogel monomer is selected from sodium alginate or sodium hyaluronate; the crosslinking agent of sodium alginate hydrogel is CaCl2; the raw materials of hyaluronic acid silicone gel include sodium hyaluronate and medical silicone. S2. Add the prepared mixed solution into the mold and let it stand at 4~10 ℃ to solidify and form the hydrogel-like biosensor.

8. The preparation method according to claim 7, characterized in that: In step S1, The hydrogel monomer is selected from sodium alginate, and the crosslinking agent is CaCl2. The components in the hydrogel mixture are mixed in the following mass ratio: hydrogel monomer: crosslinking agent: PDA-HEA: water in a mass ratio of 6-10: 0.10-0.14: 0.010-0.014:

1. First, the hydrogel monomer is added to water and heated to dissolve. Then, a crosslinking agent is added, and after mixing, PDA-HEA is added and mixed to obtain a hydrogel mixture solution.

9. The application of the high-entropy alloy nanoenzyme PDA-HEA according to claim 4 or the PDA-HEA-based biosensor according to claim 5 in the detection of acetylcholinesterase, amino acid ester pesticides or organophosphorus pesticides; wherein the amino acid ester pesticides include one of methomyl, isoprocarb, aldicarb, and carbofuran.

10. The application according to claim 9, characterized in that: The application method of the high-entropy alloy nanozyme PDA-HEA for detecting acetylcholinesterase according to claim 4 includes the following steps: S1. Mix and incubate acetylcholinesterase solutions of known different concentrations with acetylthiocholine solutions. Add NaAc buffer, PDA-HEA, TMB solution and H2O2 solution to the incubated mixture to form the ATCh-TMB-H2O2 detection system. Measure the absorption spectrum after the reaction is complete. S2. Obtain the absorbance corresponding to different concentrations of acetylcholinesterase solutions. Plot the concentration of acetylcholinesterase on the x-axis and the change in absorbance on the y-axis to obtain a standard curve of absorbance change versus concentration. S3. Take the acetylcholinesterase to be tested, detect its absorbance using the same method, and calculate its concentration by comparing it with the absorbance change-concentration standard curve.

11. The application according to claim 10, characterized in that: After irradiating the PDA-HEA with an 808 nm near-infrared laser for 4-6 minutes, proceed with steps S1-S3. The absorption spectrum measured in step S1 is measured at 652 nm.

12. The application according to claim 9, characterized in that: The application method of the high-entropy alloy nanoenzyme PDA-HEA for detecting methomyl according to claim 4 includes the following steps: S1. Mix and incubate a solution of acetylcholinesterase of known concentration with a solution of acetylthiocholine. Add different concentrations of methomyl, NaAc buffer, PDA-HEA, TMB solution and H2O2 solution to the incubated mixture to form an ATCh-TMB-H2O2 detection system. Measure the absorption spectrum after the reaction is complete. S2. Obtain the absorbance corresponding to different concentrations of methomyl solution. Plot the concentration of methomyl on the x-axis and the change in absorbance on the y-axis to obtain the standard curve of absorbance change versus concentration. S3. Take the methomyl to be tested and measure its absorbance using the same method. Calculate its concentration by comparing it with the absorbance change-concentration standard curve.

13. The application according to claim 12, characterized in that: After irradiating the PDA-HEA with an 808 nm near-infrared laser for 4-6 minutes, proceed with steps S1-S3. The absorption spectrum measured in step S1 is measured at 652 nm.

14. The application according to claim 9, characterized in that: The method for using the biosensor for detecting acetylcholinesterase according to claim 5 includes the following steps: ATCh and AChE standards of different concentrations were mixed and incubated to obtain a standard incubation solution. ATCh and the sample to be tested were mixed and incubated to obtain a sample incubation solution. The standard incubation solution and the sample incubation solution were then added dropwise to different detection units of the biosensor described in claim 5. H2O2 and TMB were then added, and the reaction was allowed to proceed fully. The color change of the gel in the detection unit was recorded. The content of AChE in the sample to be tested was determined and analyzed based on the color change of the detection unit after the addition of the standard incubation solution. The application method of the biosensor for detecting methomyl according to claim 5 includes the following steps: AChE and ATCh were mixed and incubated. The incubation solution was then dropped onto the biosensor described in claim 5. Methomyl, H2O2, and TMB were then added. Methomyl standards of different concentrations and the test sample were added to different detection units of the biosensor. After the reaction was complete, the gel color change of the detection unit was recorded. The content of methomyl in the test sample was determined and analyzed based on the color change of the detection unit after the addition of methomyl standards.

15. The application according to claim 14, characterized in that: The linear range for AChE detection is 0.1-12 mU / mL; the linear range for methomyl detection is 0.45-2 ng / mL.

Citation Information

Patent Citations

  • Platinum-based high-entropy alloy nanowire catalyst and preparation method thereof

    CN114196981A

  • Fuel battery catalyst and manufacturing method thereof

    JP2023174385A